Sedimentation Processes in the White Sea The White Sea Environment Part II (The Handbook of Environmental Chemistry, 2018)
This book presents a new perspective on the sedimentation processes in the White Sea, based on a multidisciplinary research study conducted between 2001 and 2016. It provides a comprehensive review and discusses the latest research findings on the ecosystem of this sub-arctic zone. The topics addressed include suspended particulate matter as a main source and proxy of the sedimentation processes in the White Sea; vertical fluxes of dispersed sedimentary matter and absolute masses in the White Sea; and the development history and quaternary deposits of the modern White Sea basin. The authors closely examine the abundance and species composition of microalgae associations and the environmental conditions in the bottom sediments of the White Sea, namely, heavy metal accumulation and aliphatic and polycyclic aromatic hydrocarbons. The book ends contain a summary of the key conclusions and recommendations. Together with the companion volume Biogeochemistry of the Atmosphere, Ice and Water of the White Sea: The White Sea Environment Part I, it offers an essential source of information for postgraduate students, researchers, and stakeholders alike.